GraBriyani@KRUs Kitchen - Gan, Hui Ching; Packeer Mohamed, Shafinah Farvin (Multidisciplinary Applied Research and Innovation, 2021)
Due to the global pandemic COVID-19, the use of online food ordering systems had tremendously increased. This is similar to KRUs Kitchen, a catering service company that provides ‘nasi briyani’ as its main menu during this pandemic. However, this company uses a manual way of food ordering which is tedious to be managed. Therefore, the GraBriyani@KRUs Kitchen mobile based application was proposed to provide a more systematic and efficient food ordering and delivery. This project was conducted by following the Rapid Application Development (RAD) methodology, which starts from requirements planning and ends with cutover. It was evaluated through User Acceptance Testing (UAT). The objective of this evaluation is to test the prototype whether the application is easy to use and to ensure that the application works as expected. Apart from that, the other reason is to find any errors or bugs so that it can be fixed before the final system is released. Feedback received from respondents will be used to improve the application as well. There were 34 respondents involved in the evaluation. Positive feedback was received from the respondents since they agreed that the prototype could be used to complete the tasks as it is intended for. Moreover, it was found to be useful, can be used easily and has security elements. Overall, the respondents are satisfied with the prototype. This project will be beneficial for the KRUs Kitchen’s staff, customers and runners. The KRUs Kitchen’s staff can manage the orders more efficiently and systematically, while the customers can place orders and keep track of their orders more easily. On the other hand, the runners can manage their delivery more efficiently. Most importantly, this system will help the caterer to provide better customer service to the customers.